PERAN PEMERINTAH DAERAH DALAM PENGENDALIAN KEBAKARAN HUTAN DAN LAHAN DI PROVINSI KALIMANTAN BARAT: The Role of Regional Government in Controlling Forest and Land Fires in West Kalimantan Province - Tanus, Thalia Aprianti Aresteriana; Wijiningsih, Ninuk (AMICUS CURIAE, 2025)
Forests are one of biological natural resources that provide many benefits to humans. Of the total forest land area in West Kalimantan Province, 8,389,600 hectares, some have experienced damage due to burning of forest land caused by land clearing. Forest fires must be given special attention by the Regional Government as a form of implementing regional autonomy as reflected in Law Number 23 of 2014 concerning Regional Government. The main problem in this research related to the efforts made by the Regional Government of West Kalimantan Province in controlling forest and land fires in West Kalimantan from 2019 to 2023. This research is descriptive normative legal research using secondary and primary data. then analyzed qualitatively. Data collection carried out by interviews and literature study and drawing conclusions deductively. Regional Government efforts to control forest and land fires in West Kalimantan by providing administrative sanctions and warning letters to plantation companies. The West Kalimantan regional government, in making efforts to control forest fires, has established regulations, namely West Kalimantan Provincial Regulation Number 2 of 2022 concerning Control of Forest and/or Land Fires.